Implementation of Coaching in School Principal's Academic Supervision in Junior High School - Toar, Stevanie F.; Lengkong, Jeffry Sony Junus; Rotty, Victory N. J.; Mongdong, Romi Junior (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study aims to describe the implementation of academic supervision by the principal. This study uses a qualitative approach and case study method. The location of the study was State Junior High School 1 Modoinding in South Minahasa Regency. The sources of research data were informants of the principal, homeroom teacher and subject teacher. Research data were collected using interview techniques, observation, and documentation studies and processed using qualitative data analysis techniques of the interaction model. The results of the study indicate that the implementation of coaching in academic supervision by the principal includes the principles and types of coaching; supporting factors including personal teachers, principals, and school supervisors; and inhibiting factors including human resources and non-human resources. After the discussion of the research results, it was continued by presenting research conclusions and recommendatory facilities